Inequality, Gender Gaps and Economic Growth : Comparative Evidence for Sub-Saharan Africa - Hakura, Dalia; Hussain, Mumtaz; Newiak, Monique; Thakoor, Vimal (Washington, D.C. : International Monetary Fund, 2016)
A growing body of empirical evidence suggests that inequality-income or gender related-can impede economic growth. Using dynamic panel regressions and new time series data, this paper finds that both income and gender inequalities, including from legal gender-based restrictions, are jointly negatively associated with per capita GDP growth. Examining the relationship for countries at different stages of development, we find that this effect prevails mainly in lower income countries. In particular, per capita income growth in sub-Saharan Africa could be higher by as much as 0.9 percentage points on average if inequality was reduced to the levels observed in the fastgrowing emerging Asian countries. High levels of income inequality in sub-Saharan Africa appear partly driven by structural features. However, the paper's findings show that policies that influence the opportunities of low-income households and women to participate in economic activities also matter and, therefore, if well-designed and targeted, could play a role in alleviating inequalities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet